Interdomain interactions control Ca2+-dependent potentiation in the cation channel TRPV4. - Rainer Strotmann (PLoS ONE, 2010)
Several Ca(2+)-permeable channels, including the non-selective cation channel TRPV4, are subject to Ca(2+)-dependent facilitation. Although it has been clearly demonstrated in functional experiments that calmodulin (CaM) binding to intracellular domains of TRP channels is involved in this process, the molecular mechanism remains elusive. In this study, we provide experimental evidence for a comprehensive molecular model that explains Ca(2+)-dependent facilitation of TRPV4. In the resting state, an intracellular domain from the channel N terminus forms an autoinhibitory complex with a C-terminal domain that includes a high-affinity CaM binding site. CaM binding, secondary to rises in intracellular Ca(2+), displaces the N-terminal domain which may then form a homologous interaction with an identical domain from a second subunit. This represents a novel potentiation mechanism that may also be relevant in other Ca(2+)-permeable channels.